2023
DOI: 10.1002/advs.202206191
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of 2D Materials With Circularly Polarized Light

Abstract: 2D materials (2DMs), due to spin‐valley locking degree of freedom, exhibit strongly bound exciton and chiral optical selection rules and become promising material candidates for optoelectronic and spin/valleytronic devices. Over the last decade, the manifesting of 2D materials by circularly polarized lights expedites tremendous fascinating phenomena, such as valley/exciton Hall effect, Moiré exciton, optical Stark effect, circular dichroism, circularly polarized photoluminescence, and spintronic property. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 231 publications
(406 reference statements)
0
12
0
Order By: Relevance
“…This is supported by previous reports that demonstrated that CD spectral shape, peak position, and wavelength in which the CD signal crosses zero are all affected by changes in the crystal orientation of the 2D (or 1D) phases. [26,101,102] In light of these results, we demonstrate that the choice of solvent used for the deposition of chiral 2D perovskite thin film impacts the anisotropy factor of CD, which can have implications for the integration of this material in chiroptical devices.…”
Section: Circular Dichroism Responsementioning
confidence: 90%
“…This is supported by previous reports that demonstrated that CD spectral shape, peak position, and wavelength in which the CD signal crosses zero are all affected by changes in the crystal orientation of the 2D (or 1D) phases. [26,101,102] In light of these results, we demonstrate that the choice of solvent used for the deposition of chiral 2D perovskite thin film impacts the anisotropy factor of CD, which can have implications for the integration of this material in chiroptical devices.…”
Section: Circular Dichroism Responsementioning
confidence: 90%
“…Plasmonic materials with high energy ionized states, perform unique characteristics including high conductivity, light and magnetic actability due to strong plasmonic coupling, resulting superior optoelectronic and magnetoelectric effects. [ 26 ] In other words, the distribution, transport and energy of electrons in plasma state can be effectively affected by light. The use of electron trapping device equipped with semiconducting transistor or other electrode material further collected the electrons.…”
Section: Cpl Detectorsmentioning
confidence: 99%
“…The latter is important because, due to the everincreasing demand of higher processing speeds at lower power consumption, the employment of photonic integrated circuits has become a necessity for the advancement of the semiconducting industry. Among the studied systems, graphene and the possibility of its utilization in valley-and spin-tronics has contributed to the increased interest in the interplay between light and electrical transport in mesoscale devices [13][14][15] , in a bid to utilize chiral or valley-selected electrons as quantuminformation-carrying agents. Proposals introduced in the last decade to miniaturize and integrate conventional electronics with optics involve the implementation of modulators, couplers and filters in reduced scale, both based on graphene 13 , conventional semiconductors 16 , or hybrids of these two materials 17 .…”
mentioning
confidence: 99%
“…Because our devices are conducting, they can also act as electrodes for electric-field-tunable carbon-based polarizers, such as azo-group liquid crystal 35,36 , effectively enabling an all-carbon method to locally control the circular polarization of light. Such a technology is fundamental for the implementation of valleytronics in integrated devices, whose carrier population selection currently relies on optical pumping with circularly polarized light 15,37,38 .…”
mentioning
confidence: 99%